The key genes underlying pathophysiology association between the type 2‐diabetic and colorectal cancer. Issue 11 (15th June 2018) - Peng, Wen‐Fang; Bai, Feng; Shao, Kan; Shen, Li‐Sha; Li, Hui‐Hua; Huang, Shan
Abstract : Although diabetes mellitus (DM) is reported as an independent risk factor for colorectal cancer (CRC) in many researches, the underlying pathophysiology is still unclear. We investigated the differentially expressed genes (DEGs) for the diabetes and CRC to reveal the underlying pathophysiological association between the type 2‐diabetic (T2D) and CRC. Gene expression profiles for T2D (GSE55650), CRC (GSE8671), and Metformin treated cell lines (GSE67342) were downloaded from GEO database. The DEGs between T2D samples and their control samples were identified with t ‐test and variance analysis. After cluster analysis and functional enrichment analysis, protein‐protein interaction (PPI) network was constructed to find potential genes for diabetes and CRC in Metformin's treatment. Totally, we identified 583 overlapped genes, 169 common DEGs, and 414 independent DEGs between T2D and CRC samples. The common genes contained 89 up‐regulated (DEGs1) and 80 down‐regulated genes (DEGs3); and independent DEGs contained 270 down‐regulated genes (DEGs4) in diabetes and 144 down‐regulated genes (DEGs2) in CRC. In enrichment analysis, the Ribosome pathway was significantly enriched by the independent DEGs. The common genes were mainly enriched in some inflammatory related pathways. Two target genes of Metformin were significantly interacted with six hub genes (HADHB, NDUFS3, TAF1, MYC, HNFF4A, and MAX) with significant changes in expression values ( P  < 0.05, t ‐test). To summary, it is suggested that the six hub genes might play important roles in the process of Metformin treatment for diabetes and CRC. However, specific pathology remains to be further studied. Abstract : We identified six genes (HADHB, NDUFS3, TAF1, MYC, HNFF4A, andMAX) which might play important biological roles in Metformin's treatment of diabetes and CRC. Most of the six genes were novel DEGs identified in Metformin‐treated samples from diabetes and CRC patients. Together with the enriched pathways in the present study, we were able to describe the rough relationships of DW and CRC at molecular level. However, more research, especially experimental research was in need to verify the specific functions of every gene. Our discovery might promote the understanding of the development of diabetes toward CRC and provide reference for further exploration of treatment for CRC.